2022
DOI: 10.1037/pas0001164
|View full text |Cite
|
Sign up to set email alerts
|

Replication and longitudinal measurement invariance of the PTCI-9.

Abstract: Inflexible negative trauma-related cognitions are a common consequence of trauma exposure and an important indicator of posttraumatic stress disorder. One common measure of trauma-related cognitions is the 36-item Posttraumatic Cognitions Inventory (PTCI; Foa et al., 1999). Recently, a nine-item abbreviated version was developed (PTCI-9; Wells et al., 2019), which may be a reliable alternative with improved model fit. The present study examined the latent factor structure of the PTCI and PTCI-9 in a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The analysis revealed that the 3-factor structure best fitted the data. This is the same as the Wells' PTCI-9 structure model and previous studies that have confirmed 3 factors structure 15,16,23,24 . Although the literature supports the 3 factors model for PTCI-9, the PTCI did not fulfill a consistent factor structure, nor consistent validity in recent studies 23 .…”
Section: Structuresupporting
confidence: 79%
See 1 more Smart Citation
“…The analysis revealed that the 3-factor structure best fitted the data. This is the same as the Wells' PTCI-9 structure model and previous studies that have confirmed 3 factors structure 15,16,23,24 . Although the literature supports the 3 factors model for PTCI-9, the PTCI did not fulfill a consistent factor structure, nor consistent validity in recent studies 23 .…”
Section: Structuresupporting
confidence: 79%
“…Before PTCI-9 development, PTCI was used with some revisions; for example, researchers in Northern Ireland removed 8 items (PTCI with 25 items); in Korea removed 5 items (PTCI with 28 items), and in China removed 4 items (PTCI with 29 items) to fit the structure 8,13,14 . Currently, there is agreement that PTCI-9 is a promising alternative measure of PTCI 23,24 . Although in Wells' study, every 3 subscales of the original PTCI-9 include 3 items; in this research, "item 3" loaded in the Self subscale instead of the Self-blame subscale.…”
Section: Structurementioning
confidence: 99%
“…One of the primary concerns of the PTCI and PTCI-9 is their dimensionality, given their highly interconnected relationship. Only one recent study examined the bifactor models of the PTCI and PTCI-9 (Byllesby et al, 2022) and suggested a multidimensional structure due to low omega hierarchical values (the PTCI, omega H ranges from .50 to .70; the PTCI-9, omega H ranges from .76 to .77). Based on our current comparison of the competing models of the PTCI and PTCI-9, interpreting total scores is more appropriate than using the subscale scores, especially for the PTCI-9.…”
Section: Discussionmentioning
confidence: 99%